2021
DOI: 10.3390/app11052350
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Metal(loid)s at the Sediment-Water Interface in an Aquaculture Lagoon Environment (Grado Lagoon, Northern Adriatic Sea, Italy)

Abstract: The cycling of metal(loid)s at the sediment–water interface (SWI) was evaluated at two selected sites (VN1 and VN3) in an active fish farm in the Grado Lagoon (Northern Adriatic, Italy). In situ experiments using a transparent benthic chamber and the collection of short sediment cores were performed, to investigate the behavior of metal(loid)s in the solid (sediments) and dissolved (porewaters) phases. Total and labile concentration of metal(loid)s were also determined in sediments, to quantify their potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The study focuses on research carried out from 1982 on the Italian side of the Central and Northern Adriatic Sea (Barbanti et al, 1995;Bertuzzi et al, 1996;Bertuzzi et al, 1997;Cermelj et al 1997;Cermelj et al, 2001;Frascari et al, 1995;Giordani and Hammond, 1985;Giordani et al, 1994;Giordani et al, 1996;Hammond et al, 1999;Spagnoli and Bergamini 1997;Tahey et al, 1996;Spagnoli et al, 2010) (Figure S3, Table S1). Previous papers on dissolved benthic fluxes in the Adriatic basin have addressed transitional ecosystems (Covelli et al, 1999;Covelli et al, 2011;De Vittor et al, 2012;Petranich et al, 2018;Petranich et al, 2021), specific elements (Ciceri et al, 1992;Covelli et al, 2008;Emili et al, 2011;Emili et al, 2014;Epping and Helder, 1997;Zago et al, 2000), or else have reworked previous data (Cermelj et al, 1997, Ogrinc andFaganeli, 2006;Testa et al, 2020) or examined other areas of the Adriatic Sea not considered in this paper (Baric et al, 2006;Giordani et al, 2002). This work addresses nutrients and DIC as well as iron and manganese fluxes at the SWI in the Northern and Central- Western Adriatic Sea.…”
Section: -mentioning
confidence: 99%
“…The study focuses on research carried out from 1982 on the Italian side of the Central and Northern Adriatic Sea (Barbanti et al, 1995;Bertuzzi et al, 1996;Bertuzzi et al, 1997;Cermelj et al 1997;Cermelj et al, 2001;Frascari et al, 1995;Giordani and Hammond, 1985;Giordani et al, 1994;Giordani et al, 1996;Hammond et al, 1999;Spagnoli and Bergamini 1997;Tahey et al, 1996;Spagnoli et al, 2010) (Figure S3, Table S1). Previous papers on dissolved benthic fluxes in the Adriatic basin have addressed transitional ecosystems (Covelli et al, 1999;Covelli et al, 2011;De Vittor et al, 2012;Petranich et al, 2018;Petranich et al, 2021), specific elements (Ciceri et al, 1992;Covelli et al, 2008;Emili et al, 2011;Emili et al, 2014;Epping and Helder, 1997;Zago et al, 2000), or else have reworked previous data (Cermelj et al, 1997, Ogrinc andFaganeli, 2006;Testa et al, 2020) or examined other areas of the Adriatic Sea not considered in this paper (Baric et al, 2006;Giordani et al, 2002). This work addresses nutrients and DIC as well as iron and manganese fluxes at the SWI in the Northern and Central- Western Adriatic Sea.…”
Section: -mentioning
confidence: 99%
“…Petranich et al [3] evaluated the cycling of metal(loid)s at the sediment-water interface (SWI) in an active fish farm in a Northern Adriatic lagoon environment by means of in situ experiments using a transparent benthic chamber. Although sediments showed high total metal(loid) concentrations and moderate effluxes at the SWI, the results suggested that they are barely remobilized from the sediments and would not constitute a threat to the aquatic trophic chain in the fish farm.…”
mentioning
confidence: 99%